A Study of Histomorphology of Ovarian Neoplasms (Journal of Dhaka Medical College, 2018)
Background: Ovarian malignancy is one of the most common causes of cancer deaths in females in Bangladesh. Due to poor early symptoms and lack of screening protocol, it is detected later in the clinical course of the disease. It is also one of the most treatable tumors because majorities are sensitive to chemo-radiation. An accurate histology is often a critical factor in achieving optimum treatment response.Objective: To study the frequency and histological patterns of neoplastic ovarian lesions.Methodology: A retrospective cross sectional study was done. We analyzed the data compiled from ovarian lesions biopsied and reported in a private diagnostic center from January 2008 to December 2015.Results: Out of 231 ovarian specimens only 66 were neoplastic lesions, while the rest were nonneoplastic cysts. The age range was 9 to 65 years with a mean of 36.58 ±10.45. 73 percent (48) were benign, 6.01 percent (4) were borderline and 21.21 percent (14) were malignant. Surface epithelial tumors were the most common ovarian neoplasm (n=48; 72.73%) followed by germ cell tumor (n=14; 21.21%) and sex cord stromal tumor (n=4; 6.01%). Serous cystadenoma was the commonest benign tumor (23) followed by dermoid cyst (11), and mucinous cystadenoma (10). Only 4 borderline malignant tumors were found; 03 of which were mucinous and 01 serous. The number of malignant tumor was 18. Malignant mucinous neoplasm was the commonest, in both invasive carcinoma (05) and borderline group (03).Conclusion: Benign ovarian neoplasm was more common than malignant ones. Surface epithelial tumor was the frequent group followed by germ cell tumor. Serous cystadenoma was most common among benign tumors whereas mucinous cystadenocarcinoma was the commonest malignant tumor.J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 25-28